Perencanaan Bangunan TPS3R Di Kelurahan Menteng Kota Palangka Raya - Ferdy, Muhammad; Dewantoro, Dewantoro; Nuswantoro, Waluyo (Jurnal Basement : Jurnal Teknik Sipil, 2025)
Currently, the waste generation in Menteng Subdistrict, Palangka Raya City reaches 30.48 tons per day. This has resulted in waste piling up and scattering at the Temporary Disposal Site (TPS). To address this issue, efforts are needed to sort, process, and reduce waste by providing a Waste Processing Facility for Reduce-Reuse-Recycle (TPS3R). The study was conducted through observations of waste management facilities and an analysis of waste generation and composition data. The design was developed based on the TPS3R Technical Guidelines. The cost estimation was calculated according to the Ministry of Public Works and Housing's Standard Unit Prices (AHSP KemenPUPR) and the local labor and material unit prices. The study produced a design and cost estimate for the construction of TPS3R in Menteng Subdistrict, Palangka Raya City. The TPS3R facility will cover an area of 200 m², consisting of: Sorting, Receiving, and Transporting Residual Waste area: 20 m², Office: 10 m², Storage: 20 m², Processing Area: 100 m², Residual Waste Storage: 10 m², Packaging Area: 30 m², Recyclable Material Storage: 10 m². The estimated construction cost is Rp 799,766,000. A total of three TPS3R buildings are needed to accommodate the waste generation in Menteng Subdistrict, Palangka Raya City